2019
DOI: 10.3390/cells8121480
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Epigenetic Therapy of Decitabine and Suberoylanilide Hydroxamic Acid Exerts Anti-Neoplastic Effects in Acute Myeloid Leukemia Cells

Abstract: Atypical epigenetic processes including histone acetylation and DNA methylation have been identified as a fundamental theme in hematologic malignancies. Such mechanisms modify gene expression and prompt, in part at least, the initiation and progression of several malignancies including acute myeloid leukemia. In the current study we determined the effects of treating KG-1 and U937 acute myeloid leukemia (AML) cells, in vitro, with the HDAC inhibitor, suberoylanilide hydroxamic acid (SAHA), or with a DNMT inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…We found that treatment of HULP cells with SAHA decreased cell proliferation, as demonstrated by decreased PCNA protein expression. These findings suggest an antiproliferative effect of SAHA treatment on UL, as was previously described in other tumors (31)(32)(33). Additionally, the cell cycle regulatory genes CCND1 and C-MYC were down-regulated after SAHA treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that treatment of HULP cells with SAHA decreased cell proliferation, as demonstrated by decreased PCNA protein expression. These findings suggest an antiproliferative effect of SAHA treatment on UL, as was previously described in other tumors (31)(32)(33). Additionally, the cell cycle regulatory genes CCND1 and C-MYC were down-regulated after SAHA treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Suberoylanilide hydroxamic acid (SAHA), or vorinostat, is a competitive inhibitor of class I and class II HDAC (26) that is used as an anticancer drug to treat different types of tumors (27,28). One of the well-characterized biochemical effects of SAHA is increased accumulation of acetylated core histones caused by inhibition of HDAC activity (29,30), which blocks cell proliferation and tumor growth in hepatoid adenocarcinoma (31), myeloid leukemia (32), and prostate cancer (33).…”
mentioning
confidence: 99%
“…The pellet was resuspended in incubation buffer and stained with Annexin V and propidium iodide (PI) following the manufacturer's instruction (Annexin V-FITC Apoptosis Detection Kit; Abcam). Cells were then analyzed by flow cytometer using the BD Accuri C6 Plus Software as previously described [50,51]. Living cells are stained negative for both Annexin-V and PI.…”
Section: Cell Apoptosis Detection By Annexin V/pi Stainingmentioning
confidence: 99%
“…Similarly, aberrant DNA methylation often silences the transcription of tumor-suppressor genes and is considered a hallmark of myeloid neoplasms [ 12 ]. The crosstalk between DNA methylation and histone modifications has been reported widely [ 13 ]. The combined clinical use of histone deacetylase inhibitors (HDACi) and a DNA methylation agent (HMA) enhances the efficacy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%